Type and character of pre-match warm-up in football and its effect on lactate level in blood - Jaszczanin, J.; Buryta, R.; Krupecki, K.; Jaszczanin, N.; Cieszczyk, P. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of this work is to define a type and character of pre-match warm-up in football, its effect on lactate level in blood and also an attempt of defining optimal break time between the end of warm-up and participation in the match. Investigation involved Stal Szczecin football team (playing in the fourth division) consisting of 15 football players.